2022
DOI: 10.1002/fsn3.3052
|View full text |Cite
|
Sign up to set email alerts
|

Study on the hypolipidemic effect of Inonotus obliquus polysaccharide in hyperlipidemia rats based on the regulation of intestinal flora

Abstract: The purpose of this study was to observe the effect of Inonotus obliquus polysaccharide (IOP) on blood lipids and its regulation on the intestinal flora in hyperlipidemia rats, and explore the modern biological connotation of IOP in reducing blood lipids. In this study, we obtained the crude IOP by the water extraction and alcohol precipitation method, and then classified it by DEAE ion‐exchange chromatography to obtain the acidic I. obliquus polysaccharide (IOP‐A). After the administration of the IOP‐A, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…DNA sequencing of caecal microbiota revealed that the ameliorative effects of IOP on obesity are through modification of the microbiota metabolism, particularly an increase in butyrate-production-associated bacteria Lactobacillus and Bacteroidales S24-7, as well as short-chain fatty acid-producing bacteria Holdemanella and Ruminococcaceae_UCG-014 (Yu et al 2020 ). Furthermore, IOP can significantly reduce serum total cholesterol (TC), triglycerides (TG), and low-density lipoprotein-cholesterol (LDL-C) contents, while increasing high-density lipoprotein-cholesterol (HDL-C) content both in vitro in oleic acid-induced HepG2 cells and in vivo in mice fed with a high-fat diet (Yang et al 2021 ; Lin et al 2023 ). A successful decrease in the weight gain of mice induced by a high-fat diet was also observed after 10 weeks of IOP treatment (Yang et al 2021 ).…”
Section: Bioactive Compounds and Their Therapeutic Properties Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA sequencing of caecal microbiota revealed that the ameliorative effects of IOP on obesity are through modification of the microbiota metabolism, particularly an increase in butyrate-production-associated bacteria Lactobacillus and Bacteroidales S24-7, as well as short-chain fatty acid-producing bacteria Holdemanella and Ruminococcaceae_UCG-014 (Yu et al 2020 ). Furthermore, IOP can significantly reduce serum total cholesterol (TC), triglycerides (TG), and low-density lipoprotein-cholesterol (LDL-C) contents, while increasing high-density lipoprotein-cholesterol (HDL-C) content both in vitro in oleic acid-induced HepG2 cells and in vivo in mice fed with a high-fat diet (Yang et al 2021 ; Lin et al 2023 ). A successful decrease in the weight gain of mice induced by a high-fat diet was also observed after 10 weeks of IOP treatment (Yang et al 2021 ).…”
Section: Bioactive Compounds and Their Therapeutic Properties Of ...mentioning
confidence: 99%
“…In addition, lipid synthesis-related genes, sterol regulatory element-binding protein-1C (SREBP-1C), acetyl-coenzyme A carboxylase (ACC), and fatty acid synthase (FAS), were found to be lower in HFD-treated-C57BL/6J mice that received IOP intervention as compared to untreated groups (Yang et al 2021 ). Instead, IOP treatment was observed to reverse the downregulated expressions of adenosine monophosphate-activated protein kinase (AMPK) in obese mice (Yang et al 2021 ) and increased cholesterol 7 alpha-hydroxylase (CYP7A1) expressions (Lin et al 2023 ), which is an enzyme involved in the main pathway for cholesterol removal from the body (Wang et al 2018 ).…”
Section: Bioactive Compounds and Their Therapeutic Properties Of ...mentioning
confidence: 99%
“…Because of its multi‐component and multi‐target intervention characteristics, traditional Chinese medicine has emerged as a focal point in the prevention and treatment of obesity. The active ingredients found in traditional Chinese medicine, including flavonoids (Song et al, 2019; Zheng et al, 2018), alkaloids (He et al, 2017; Ning et al, 2020), polysaccharides (Lin et al, 2023; Sang et al, 2021), and polyphenolic compounds (Wang et al, 2019; Xu et al, 2020), possess the ability to regulate bile secretion, reduce cholesterol levels, enhance immune function, inhibit inflammatory responses, and promote the stability of intestinal flora. However, further in‐depth and accurate investigation is required to elucidate the precise mechanism by which traditional Chinese medicine regulates intestinal flora structure and improves metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%